ปัจจัยที่มีผลต่อการตัดสินใจในการปลูกลำไยของเกษตรกรในเขตพื้นที่อำเภอพร้าว จังหวัดเชียงใหม่ - ภาวิณี ศรีทองแท้ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2017)
This research aims to study the factors that influence the farmers to plant the longan and study the problems and suggestions in planting longan of the farmers in Phrao, Chiangmai. The data collections are collected from 500 sampled farmers in Phrao, Chiangmai by using the questionnaires. Descriptive statistics and Logit model with Maximum likelihood Estimates are applied in the analysis of this study. As a results, mostly farmers (88.4%) are male with age 56-65 years old (53.2%), primary school education (36.2%), being married (91.6%), and being Buddhism (87.1%). The farmers earn the average of family income around 151,692 baths per year and other incomes around 35,715 baths per year. Moreover, mostly sampled farmers have agricultural areas 5-10 hectares (37.2%), living areas and others are less than 5 hectares. In family member case, the majority of sampled farmers have 2-4 people in their families (70.8%), followed by 3 working members in each family (63.8%). The farmers have experience in farming for 10-20 years (56.6%) and take part in the meeting of training to plant the longan maximum 2-3 times (44.4%). The researcher found that the experience in planting the longan is the most significant factor to lead the farmers in planting more longan (46.56%), followed by the transportation, the price, the area for the planting, the market for selling longan, and the catalyst. These factors influence farmers to plant more longan 34-38% in orders. Plus, the persuasion and suggestion from close people such as, family members and friends, or even other factors like gender and the number of working people cause the farmers to plant more longan 21-29%. Lastly, the money for investment is the least important factor for the farmers in decision of planting the longan(18.84%). Furthermore, the researcher discovered the problems and obstacles in planting the longan from the farmers; they are problems in the manufacture, market, and economics. However, the farmers suggested that the government should set the price of longan; make the price not to be too fluctuating. Finally, the government should control the price of fertilizer and chemicals; make the price not to be too expensive.